Sensory Stimulation Activities Improving Quality of Life of Elderly People in Elderly Communities - Aniek Puspitosari; Ninik Nurhidayah (Jurnal Penelitian Pendidikan IPA, 2023)
The aging process has an impact on social, economic and health aspects of life. The presence of elderly people with all health problems causes a decrease in quality of life. One effort to overcome physical health problems, especially sensory organs, is by providing sensory stimulation activities to the elderly. Sensory stimulation activities by stimulating gustatory/oral motor, visual, olfactory, tactile, auditory, vestibular and proprioceptive. This study aims to determine the effect of providing sensory stimulation activities on the quality of life of the elderly. The research method was a pre-experimental one group pretest-posttest design with a sample size of 44 elderly people in the elderly community in RW 8 area of ​​Kemiri Village, Kebakkramat, Karanganyar. Intervention by providing 10 sensory stimulation activities. Quality of life is measured by the World Health Organization Quality of Life (WHOQOL-BREF) before and after 8 section. The data analysis method uses Paired Sample T Test. The results showed Paired sample t-test Asmyp Sig. (2-tailed) = 0.000, which means that the p-value < α (0.05), which means that the Sensory Stimulation activity intervention has an effect on the quality of life of the elderly in the elderly community in RW 8 area of ​​Kemiri Village, Kebakkramat, Karanganyar.